Macromolecular Transport in the Arterial Wall: Alternative Models for Estimating Barriers - Lee, Kwangdeok; Saidel, Gerald M.; Penn, Marc S. (Annals of biomedical engineering, 2005)
Early atherosclerosis, or atherogenesis, is characterized by the abnormal accumulation of plasma-borne macromolecules (e.g., LDL) in the arterial intima. The change of barrier characteristics of tissue in the arterial wall requires evaluation of macromolecular transport across the endothelial cell layer (ECL) and internal elastic lamina (IEL), the luminal and abluminal boundaries of the arterial intima, respectively. In this study, alternative mathematical models are derived from dynamic mass balances to describe macromolecular transport across the arterial wall. One model considers each medial layer as a spatially lumped compartment, whereas another model consists of a spatially lumped intima and spatially distributed media. Model simulations of a tracer concentration distribution in the arterial wall are compared with concentration distributions of horseradish peroxidase (HRP) after i.v. injection in mice. For each model, optimal parameter values are obtained that yield model outputs matching the data well for two different HRP circulation times. The model parameter estimates show that the ECL is the major barrier for macromolecular transport across the normal arterial wall. Sensitivity analysis indicates that the parameter estimates of the transport coefficients of the ECL and IEL are well determined. Optimal circulation times are determined and expected to yield improved precision of parameter estimates in future experiments to reflect disease progression.